A new high-resolution groundwater isoscape for south-east Germany: insights from differences in relation to precipitation - A. Gaillard; R. van Geldern; J. A. C. Barth; C. Stumpp (Hydrology and Earth System Sciences)
Stable water isotopes are important tracers in understanding interactions between all compartments of the hydrological cycle. Particularly in groundwater studies, isotopes have been used to assess the recharge and origin of groundwater. Based on high-density groundwater measurements from 596 measurement stations in an area of 70 500 km2, we produced a new interpolated map of the δ18O distribution (i.e. an isoscape) in the groundwater of south-east Germany. A comparison of this groundwater isoscape to the regional long-term precipitation isoscape showed differences of up to ±2 ‰ between these two compartments. Groundwater was enriched in the light isotope 16O compared to precipitation in the alpine area, where recharge occurs mainly during winter and in recharge areas at higher altitudes. However, groundwater was enriched in the heavy isotope 18O with respect to precipitation in drier lowland regions where summer recharge, irrigation practices and aquifer types as well as evaporation processes may play a role. Further comparative studies between the stable water isotopes of precipitation and groundwater, including time series, are needed to further improve our understanding of the spatial and seasonal recharge patterns of groundwater.